Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Rewrite each subtraction equation as an addition equation.
p - 26 = - 38
z - (-72) = 35


Sagot :

Answer :

addition equation:

-38 + p = 26

35 + z = -72

-------------------------------

actual answer:

z = -37

p = -12